Odpowiedzi

2009-10-19T19:40:31+02:00
A) -2,2+3,3= 1,1
b) 1i 5/6- 1i 2/6 = 3 i 1/6
c) -3,2
d)-4,5 - 2,25 = 6,75
e)-3 i 1/6 + 5 i 5/6 =
dalej mi sie nie chce xdd
Najlepsza Odpowiedź!
2009-10-19T19:55:14+02:00
A.-2 i 1/5 + 3,3 = -2,2 + 3,3 = 1,1
b.1 i 5/6 - 3 i 1/3 = 1i 5/6 - 3 i 2/6 = - 2i 3/6 = - 2 i 1/3
c.4,3 - 7,5 = -3,2
d. -4,5 - 2 i 1/4 = - 4 i 1/2 - 2 i 1/4 = - 6 i 1/2
e.- 3 1/6 -(- 5 i 5/6) = - 3 i 1/6 + 5 i 5/6 = 3
f. 7 i 1/3 + (- 4 i 5/6) = 7 i 2/6 + (- 4i 5/6) = 2 i 3/6
g.- 5 i 4/7 - 7 = - (5 i 4/7 - 7) = 1 i 3/7
h.1,23 - 9 = - 7 ,77
i. -6-(4 i 5/9) = - 6 + 4 i 5/9 = - (10 i 5/9)
2009-10-19T22:00:50+02:00
A)=-11/5+33/10=-22/10+33/10=-11/10=-1 1/10
b)=11/6-10/3=11/6-20/6=-9/6=-3/2=-1 1/2
c)=43/10-75/10=-32/10=-3 1/5
d)=-45/10-9/4=-180/40-90/40=-270/40
e)=-19/6+35/6=-16/6
f)=22/3-29/6=44/6-29/6=15/6
g)=-39/7+49/7=10/7
h)=-7,77
i)=-6+41/9=-54/9+41/9=-13/9